Prevention of HIV transmission through breastmilk in Abidjan, Côte d'Ivoire. The ANRS 1201/1202 Ditrame Plus study - (:unkn) unknown (My University, 2005)
Breastfeeding is responsible for one third to half of perinatally acquired HIV infections in Africa. Besides antiretroviral-based interventions to reduce the risk of postnatal HIV transmission, different nutritional approaches are conceivable in modifying infant feeding practices such as complete avoidance of breastfeeding in urban settings or shortening the breastfeeding period. These interventions were evaluated within the Ditrame Plus cohort study, conducted in Abidjan, Côte d'Ivoire between 2001 and 2005. This strategy of reduction of HIV transmission through breastmilk was acceptable, safe and effective in our context. We have discussed the public health implications of our results in pointing out the difficulties linked to the operational implementation of these interventions. We have also proposed situations where this implementation could be a reality in Africa.
Keywords: African Research